CONSIDERATIONS REGARDING THE MANAGEMENT OF ORGANIZATIONAL CULTURE AT THE LEVEL OF PROFFESIONAL EMERGENCY SERVICES IN WESTERN ROMANIA - VASTAG (VLĂDUŢESCU), Irina (Studia Universitatis Babeș-Bolyai Philosophia, 2015)
No organization can be led efficiently if it is unaware of true values. Starting from this aspect, this study aims to analyse the organizational culture of professional emergency services in the Western part of Romania, a complex, social, formal, well organized and coordinated structure. Various ways of reform have been tried out; however only a few were concerned with starting change from the cultural elements, i.e. from knowledge, awareness and valuation of these elements. When collecting data, I used both qualitative and quantitative methods, and the conclusions of the research show that there are certain significant correlations between the dominant decision-making style and the cultural types, both existing and desired by the employees, according to the staff categories they belong to; and the profile of dominant rules reflects a special emphasis on the interpersonal values.